The differences in the interactive modification of interaction between target groups and personnel management tools - Tanja Gorcheva (Journal for East European Management Studies, 2005)
The harmonisation of Bulgarian and foreign entrepreneurs' concepts for personnel management is part of Bulgaria's process of transition to free market economy. On the one hand this is possible provided that Bulgarian entrepreneurs get familiar with the practices and experience of their European counterparts. On the other hand foreign investors could be more successfully attracted if they are motivated enough to actively do business in Bulgaria. The research focuses on the differences in policy modelling of the PM target groups and PM instruments in the 17 Bulgarian, 17 German enterprises and 7 Joint- Ventures operating in the markedly dynamic business environment of Bulgarian economy. – – Die Annäherung von bulgarischen und ausländischen Unternehmerkonzepten für das Personalmanagement ist Teil des Transformationsprozesses in Bulgarien in eine freie Marktwirtschaft. Auf der einen Seite ist das möglich, vorausgesetzt dass Bulgariens Unternehmer sich mit den Praktiken und der Erfahrung ihrer europäischen Kollegen vertraut machen. Auf der anderen Seite könnten ausländische Investoren erfolgreicher angezogen werden, wenn sie motiviert genug wären, aktiv in Bulgarien tätig zu werden. Die Studie konzentriert sich auf die Unterschiede in den Methoden bezüglich der Zielgruppen und Intrumente des Personalmanagements in 17 bulgarischen, 17 deutschen Unternehmen und 7 Joint-Ventures, die in der marktdynamischen Umgebung der bulgarischen Wirtschaft operieren.
Keywords: 650; Personal Management; Transition Period; Comparative Analysis; Target groups; PM-Tools